2020
DOI: 10.1101/2020.06.02.20114967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paediatric Dentistry and the coronavirus (COVID-19) response in the North East of England and North Cumbria

Abstract: Introduction: Coronavirus (COVID-19) has dramatically changed the landscape of dentistry including Paediatric Dentistry. This paper explores paediatric patient data within a wider service evaluation completed within an Urgent Dental Care Centre in the North East of England and North Cumbria over a 6-week period. Aim: To assess demand for the service, patient demographics and inform paediatric urgent dental care pathways. Main outcome methods: Data collected included key characteristics of paediatric patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Restless, crying children spread more aerosol compared to calm children, so appropriate and skillful behavior management is the first and most important basic technique to minimize the probability of SARS-CoV-2 cross-infection. Dental care to children involves various methods for behavior management, including inhaled or conscious sedation, which were a subject of controversy during COVID-19 outbreak; for example, Simpson et al ( 15 ) avoided inhalation sedation due to difficulties disinfecting the reusable nasal hoods and tubing. This led them to use non-pharmacologic behavior management techniques which they reported effective in over a third of patients who needed extraction and trauma management under local anesthesia ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restless, crying children spread more aerosol compared to calm children, so appropriate and skillful behavior management is the first and most important basic technique to minimize the probability of SARS-CoV-2 cross-infection. Dental care to children involves various methods for behavior management, including inhaled or conscious sedation, which were a subject of controversy during COVID-19 outbreak; for example, Simpson et al ( 15 ) avoided inhalation sedation due to difficulties disinfecting the reusable nasal hoods and tubing. This led them to use non-pharmacologic behavior management techniques which they reported effective in over a third of patients who needed extraction and trauma management under local anesthesia ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dental care to children involves various methods for behavior management, including inhaled or conscious sedation, which were a subject of controversy during COVID-19 outbreak; for example, Simpson et al ( 15 ) avoided inhalation sedation due to difficulties disinfecting the reusable nasal hoods and tubing. This led them to use non-pharmacologic behavior management techniques which they reported effective in over a third of patients who needed extraction and trauma management under local anesthesia ( 15 ). We have used a higher rate of non-pharmacologic behavior management during lockdown compared with the other periods, as less patients were treated with nitrous oxide (either exclusively or combined with oral sedative) at lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Carter et al have reported the acute pulpitis and periapical diseases as the most common complaints of adult and pediatric patients in urgent dental care centres of Newcastle Dental Hospital during COVID-19 [6]. Another study claimed the irreversible pulpitis and dental trauma to be the most frequent diagnoses in pediatric patients in an Urgent Dental Care Centre in the North East of England and North Cumbria [21].…”
Section: Introductionmentioning
confidence: 99%
“…6 Another study claimed the irreversible pulpitis and dental trauma to be the most frequent diagnoses in pediatric patients in an Urgent Dental Care Centre in the North East of England and North Cumbria. 21 Iran is no exception to this, and the trend seems to be the same due to 55.5% of Internet accessibility (in 2015). 22 Further, poor to the fair oral health status of the general population and especially among 35 - to 44-year-old adults in Iran could reinforce the need for urgent dental services in the country.…”
Section: Introductionmentioning
confidence: 96%